L233P mutation in the bovine leukemia virus Tax protein has impact on annexin A3 and type I collagen secretion by host cells - Tomiyasu, Takafumi; Sato, Ayuki; Mori, Hiroshi; Okazaki, Katsunori (Veterinary microbiology, 2021)
•Bovine leukemia virus Tax modulated host cell secretion of potential tumor makers.•L233-Tax stimulated annexin A3 secretion.•L233-Tax suppressed type I collagen secretion.•Both L233- and P233-Tax suppressed potentially antiangiogenic molecules secretion. Bovine leukemia virus (BLV) is the causative agent of enzootic bovine leukosis (EBL) and can be classified into two types based on the amino acid at position 233 in Tax protein, which probably plays crucial roles in leukemogenesis. We previously revealed that L233-Tax-expressing cells secreted chemoattractants for endothelial cells and formed significantly larger tumors accompanying neovascularization than P233-Tax-expressing cells in athymic mice. In the present study, comparative proteomic analysis of the culture medium of Tax-expressing cells revealed that annexin A3 and probably extracellular matrix protein 1 served as chemoattractants. Conversely, L233-Tax-expressing cells were impaired in the secretion of collagen alpha-1 (I) chain precursor, which participates in tissue tension homeostasis, leading to tumor mass development. The analysis also demonstrated that both L233-Tax- and P233-Tax-expressing cells had deficits in the secretion of potentially antiangiogenic molecules, including pigment epithelium-derived factor and collagen alpha-1 (VIII) chain, and they produced complement component 3, which might participate in tumor cell proliferation, metastasis, and immune evasion. These findings provided novel insights into prognostication of EBL and the function of Tax in leukemogenesis induced by BLV.